FACTORS THAT AFFECTING SLEEP QUALITY IN ADOLESCENTS AT TEGAL CITY - Maria Ulfah; Dwi Uswatun Khasanah; Deddy Utomo (Prodi D3 Keperawatan Tegal Poltekkes Kemenkes Semarang, 2021)
Adolescent sleep problems should be considered as a longstanding health problem in society. One group that is at high risk of experiencing sleep disorders is adolescents. This is because in adolescents there are changes in sleep patterns including insufficient sleep duration, delayed sleep time, and differences in sleep patterns on weekdays and weekends, so the quality of adolescent sleep tends to decrease. The results of sleep deprivation can, among other things, affect the physical, mental, emotional and social development of adolescents, including brain maturity and decision-making skills. The problem of sleep disorders in adolescents is difficult to enforce, this is because sleep disorders are often not conveyed by adolescents. The purpose of this study was to identify the prevalence of sleep problems and the factors that influence the quality of adolescents (18-21 years) in Tegal City. This study used a cross-sectional descriptive analytic method with 217 respondents as the sample of the study from Tegal Nursing D3 students. Collecting data through google form and using the Indonesian version of the Pittsburgh Sleep Quality Index (PSQI) questionnaire, the Mornignness-Eveningness Questionnaire (MEQ). The results showed that there was a relationship between sleep quality and chronotype type (p value: 0.00 a = 0.000). Recommendations for adolescents need education about disturbances in adolescent sleep quality